Industrial dynamics in conditions of digitalization of economy - E. V. Yakovleva; Yu. S. Ilina (Омский научный вестник: Серия "Общество. История. Современность")
This paper examines the impact of digitalization on the industry of Russian economy. The results of an analytical study of the impact of digitalization on the dynamics of manufacturing enterprises are presented. The target setting is focused on the analysis of industrial dynamics in the context of the digitalization of the economy and the identification of prerequisites for the formation of an intelligent infrastructure for technological development in industry. The relevance of the study is due to the need to modernize industrial enterprises in the digital economy by updating fixed assets and putting into operation new equipment and software products (Compass-3D, SolidWorks, Mathcad, etc.) in accordance with the pace of modern technologization